2019
DOI: 10.2147/cmar.s219178
|View full text |Cite
|
Sign up to set email alerts
|

<p>Quality of life of patients with proximal humerus metastasis treated with cement spacer</p>

Abstract: PurposeThe goal of this study was to determine whether the surgery using cement spacer could improve the quality of life of patients with proximal humerus metastasis.Patients and methodsThis is a retrospective study. The study included 34 patients who had been treated for proximal humerus metastasis between January 2010 and June 2014. The patients were divided into surgical and non-surgical group depending on whether they underwent cement spacer surgery. The patient’s quality of life (QOL) assessment is schedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Since the upper extremities do not have to bear as much weight as the lower extremities, bone cement prosthesis is strong enough to perform some daily functions of the upper extremities, such as writing, combing hair, etc. To our knowledge, this method has been reported by only a few authors (19,20) with satisfactory outcomes in the upper extremities.…”
Section: Discussionmentioning
confidence: 90%
“…Since the upper extremities do not have to bear as much weight as the lower extremities, bone cement prosthesis is strong enough to perform some daily functions of the upper extremities, such as writing, combing hair, etc. To our knowledge, this method has been reported by only a few authors (19,20) with satisfactory outcomes in the upper extremities.…”
Section: Discussionmentioning
confidence: 90%
“…To the best of our knowledge, only a few authors have reported this method, but it has shown comparable functional outcomes in upper extremities. [30][31][32] However, the majority of bone cement prostheses or nail cement spacers reported in literature are manually fabricated intraoperatively. Kneading bone cement into an epiphyseal shape is a time-consuming process that can result in inaccurate shapes.…”
Section: Discussionmentioning
confidence: 99%